Impact of Ionic Liquids on the (bio)degradability of Poly(butylene succinate)/Poly(lactic acid) blends - Delamarche, Emma; Mattlet, Agnès; Livi, Sébastien; Gérard, Jean-François; Bayard, Rémy; Massardier, Valérie (Frontiers in Materials, 2022)
Bio-based and (bio)degradable polymers constitute an important material innovation because they reduce the amount of waste materials inducing persistent microplastics and can offer similar benefits to conventional polymer materials. Poly(butylene succinate) and poly(lactic acid) blends exhibit interesting properties and can be possible alternatives to some traditional polymers. Some of their properties can be tailored by adding small proportions of ionic liquids (IL) that can act as interfacial agents between PBS and PLA. In our study, samples formulated with ionic liquids display a broader morphology with thermal properties close to the PBS/PLA reference, whereas Young’s modulus is lowered in the presence of one of the IL studied. Nevertheless, the blends have a rather different ability to (bio)degrade. Indeed, disintegration experiments show that PBS/PLA/IL exhibit higher weight losses and faster fragmentation. DSC thermograms display an important decrease of PLA melting temperature after composting experiment, indicating that PLA phases are affected the most by degradation at 58°C. Our study shows that elaborating polymer materials, for which degradation processes are preferentially located in a “predegraded” dispersed phase, can be considered as a way to speed up macroscopic (bio)degradation. In the present work, morphologies, mechanical properties as well as (bio)degradability can be tailored by adding a small amount of ionic liquids.